Organ donation and priority listing - Tan, Damian Allan (Nanyang Technological University, 2022)
The donor-priority rule has been implemented in several countries in attempts to incentivise organ donation. In this paper, we went beyond the basic donor-priority rule and compared three voucher mechanisms, namely the enhanced-priority, equal-priority, and strict ordered-priority voucher, against the donor-priority rule. These voucher mechanisms confer different priority benefits in organ allocation based on subjects’ donation decisions and voucher inheritance status. Furthermore, we explored how family consent rates differed among the voucher mechanisms. Adopting a laboratory experimental approach, our findings revealed that inheriting extended priority benefits will have a crowding-in effect on donation rates in the enhanced-priority voucher mechanism, relative to the equal-priority mechanism. Additionally, when family consent is accounted for, donation rates in the enhanced-priority and strict ordered-priority mechanisms are larger than in the benchmark. Taken together, our results show some support for further modification of the existing donor-priority rule and extended voucher mechanism in organ donation and allocation policies.